Green-Synthesized NiFe₂O₄-CQDs Composite for Sensitive Electrochemical Detection of Acetaminophen and Caffeine - Vo, Chau Ngoc Anh; Do, Mai Nguyen; Nguyen, Quang Man; Pham , Thi Huyen Thoa; Tran , Ngoc Tuyen (Hue University Journal of Science: Natural Science, 2025)
In this study, a NiFe2O4-CQDs composite was synthesized and utilized to modify a glassy carbon electrode (GCE) for the simultaneous electrochemical detection of acetaminophen (ACP) and caffeine (CFE). The composite material was characterized using various techniques, including FTIR and PL spectroscopy, confirming its suitability for electrochemical applications. The DP-ASV method was employed to determine the limit of detection (LOD) for ACP and CFE, which were found to be 0.35 μM and 0.34 μM, respectively. The electrochemical method exhibited a wide linear range from 0.5 μM to 11.9 μM for both analytes. Optimized experimental conditions, including accumulation potential, accumulation time, and pulse amplitude, contributed to high sensitivity, reproducibility, and accuracy in detecting these compounds. Recovery studies in pharmaceutical samples demonstrated reliable results, with recoveries ranging from 94.2% to 103.2%. These findings suggest that the NIF-CQDs-modified GCE is a promising candidate for rapid and accurate electrochemical analysis of ACP and CFE in real-world applications.